The Enduring Value of Research in Medical Education - Juliana Bonilla-Velez; Mariah Small; Raul Urrutia; Gwen Lomberk (University Library System, University of Pittsburgh, 2017)
Evidence-based medicine (EBM) relies on scientific data to guide diagnosis and treatment and is recognized as the current paradigm in medicine. Accordingly, every current and future physician should be knowledgeable about its principles and methodologies. Embracing research and EBM is essential to modern clinical practice; however, trainees and physicians still struggle with the value of research-related courses and knowledge on epidemiology and research methodology is often poor. In this article we provide a cogent discussion of the importance of research as an indispensable discipline in medical education through a detailed analysis of the literature. We review the evolution of medicine towards EBM and discuss the myriad of benefits that research has on medical careers, leadership roles, mentoring relationships, social networking, and personal growth and development. Participation in research contributes to medicine, public health, and society while simultaneously allowing the achievement of a high level of personal satisfaction